The home, nations and empires, and ephemeral exhibition spaces : 1750-1918 - Bauer, Dominique; Murgia, Camilla, 1977- (Amsterdam University Press, 2021)
"This book explores ephemeral exhibition spaces between 1750 and 1918. The chapters focus on two related spaces: the domestic interior and its imagery, and exhibitions and museums that display both national/imperial identity and the otherness that lurks beyond a country's borders. What is revealed is that the same tension operates in these private and public realms; namely, that between identification and self-projection, on the one hand, and alienation, otherness and objectification on the other. In uncovering this, the authors show that the self, the citizen/society and the other are realities that are constantly being asserted, defined and objectified. This takes place, they demonstrate, in a ceaseless dynamic of projection versus alienation, and intimacy versus distancing." -- Back cover.
Keywords: Exhibitions -- History.; Art -- Exhibition techniques -- History.; Display of collectibles -- History.; Museum exhibits -- History.; Art -- Techniques d'exposition -- Histoire.; Objets exposés -- Histoire.; Expositions -- Histoire.; Art & design styles: Romanticism.; Museology and heritage studies.; Social and cultural history.; ART / History / Romanticism.; ART / Museum Studies.; HISTORY / Social History.; Museum exhibits; Exhibitions; Display of collectibles; Art -- Exhibition techniques; ephemeral exhibition spaces, domestic spaces, empire, nation state, otherness.; Electronic books.; History